(untitled) (Papeles, 2023)
This paper describes a series of regulations and policies deployed by the Argentine state during the period 2012-2022 in order to guarantee the rights of transvestites, transgender and non-binary people. Firstly we introduce the perspective of human rights, considering that it is the most appropriate framework for the analysis of the subject, then we analyze some theoretical concepts that we resort to for the analysis, such as social recognition, equality and affirmative actions. In second place we describe in detail the Gender Identity Law, the presidential decree that recognizes non-binary identity and the Law for the Promotion of Access to Formal Employment for Transvestites, Transsexuals and Transgender People "Diana Sacayán-Lohana Berkins", as well as the background in which its implementation took place in Argentina. Finally, we carried out an analysis of the impact that some of the main detailed measures had on the recognition of trans people and on the improvement of their living conditions. To do this, we take as input research developed by public agencies and civil society organizations that allow us to account for the scope of the policies.